Analysis of Chaotic Image Encryption Using 1D Logistic Map, 2D Arnold Cat Map and 3D Arnold Cat Map (International Journal of Scientific Research and Management (IJSRM), 2015)
Analyzing the randomness, complexity and efficiency of chaotic image encryption using 1D Logistic map, 2D Arnold cat map or 3D Arnold cat map is proposed here. The keys for the encryption process are generated from the biometric image of the sender. Initially the biometric fingerprint image of the sender is captured using a scanner, which is preprocessed to the grey level image. By using an efficient technique on the grey level image, the initial condition for the 1D Logistic map and the keys for the encryption are generated. The keys are Feature Vector, transform orders and angles for Dual Parameter Fractional Fourier Transform. The key generation process is followed by the encryption process, which includes randomization using chaotic map, transformation using DPFrFT and decomposition using Hessenberg Decomposition. The resulting image after the three processes undergoes inverse Dual Parameter Fractional Fourier Transform to get the encrypted image. The decryption process is the reverse of encryption process. The analyses is conducted using Histogram Analysis, Correlation Analysis, Information Entropy, NPCR and UACI